PATIENT'S PERCEPTION OF HIP AND KNEE OSTEOARTHRITIS IN A HOSPITAL IN JAMBI CITY - Humaryanto, Humaryanto; Iskandar, Mirna; Simanjuntak, Patrick William Gading; Justitia, Budi; Mulyadi, Deri (Medical Dedication (medic) : Jurnal Pengabdian kepada Masyarakat FKIK UNJA, 2025)
Osteoarthritis (OA) is a degenerative joint disease, primarily affecting the elderly, and is classified into primary OA (with no specific cause) and secondary OA (caused by other diseases or conditions). Although it cannot be cured, appropriate management can control the symptoms and prevent disease progression. This study aims to assess the perception and knowledge of hip and knee OA patients in Jambi City using the Osteoarthritis Knowledge Scale (OAKS) instrument. Data were obtained from 87 patients at Kambang General Hospital: 54 filled out the Knee OAKS and 33 for Hip OAKS. The results showed that patients' understanding of general knowledge about OA was high (84%), but knowledge related to prevention was significantly lower (44%). Knowledge regarding treatment and symptom management was moderate (68.2%), and understanding of healthy lifestyle behaviors was 53%. These findings indicate a significant gap in patient knowledge, particularly regarding preventive measures and lifestyle modifications. Therefore, targeted educational interventions are crucial to improve patient understanding, enhance self-management, and ultimately achieve better clinical outcomes in managing OA. Keywords: Osteoarthritis, Patient Knowledge, OAKS, Health Education, Perception